A non-monotone line search multidimensional filter-SQP method for general nonlinear programming - Gu, Chao; Zhu, Detong (Numerical algorithms, 2011)
In this paper, we propose a non-monotone line search multidimensional filter-SQP method for general nonlinear programming based on the Wächter–Biegler methods for nonlinear equality constrained programming. Under mild conditions, the global convergence of the new method is proved. Furthermore, with the non-monotone technique and second order correction step, it is shown that the proposed method does not suffer from the Maratos effect, so that fast local convergence to second order sufficient local solutions is achieved. Numerical results show that the new approach is efficient.